2015
DOI: 10.1007/s11427-015-4956-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of sister chromatid cohesion during the mitotic cell cycle

Abstract: Orderly execution of two critical events during the cell cycle--DNA replication and chromosome segregation--ensures the stable transmission of genetic materials. The cohesin complex physically connects sister chromatids during DNA replication in a process termed sister chromatid cohesion. Timely establishment and dissolution of sister chromatid cohesion is a prerequisite for accurate chromosome segregation, and is tight regulated by the cell cycle machinery and cohesin-associated proteins. In this review, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 110 publications
0
14
0
Order By: Relevance
“…40 And recently it was shown that overexpression of SUV4-20H2 rescued the cohesin and H4K20me3 defects of Rb-depleted cells. 41 Since replication defects could very well lead to cohesin defects, 42 our data suggest that cohesin phenotypes in Rbdevoid cells might be secondary to replication.…”
Section: Discussionmentioning
confidence: 80%
“…40 And recently it was shown that overexpression of SUV4-20H2 rescued the cohesin and H4K20me3 defects of Rb-depleted cells. 41 Since replication defects could very well lead to cohesin defects, 42 our data suggest that cohesin phenotypes in Rbdevoid cells might be secondary to replication.…”
Section: Discussionmentioning
confidence: 80%
“…Alterations of TP53 are predictive for BUC recurrence and are markedly associated with an unfavorable prognosis after radical cystectomy 28,29. GO enrichment analysis for biological processes demonstrated that BUC tumors were associated with mitotic recombination, sister chromatid segregation, and mitotic sister chromatid segregation, all of which are related to cell cycle regulation 3032. Our results, moreover, are supported by the study of Guo et al,33 which identified that genes involved in sister chromatid segregation were frequently altered in bladder cancer via whole-genome and whole-exome sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…During interphase, cohesin mediates the formation of chromosome loops that impact transcription (11). During S phase, cohesin physically links replicated chromosomes to establish sister-chromatid cohesion (12,13), which is a prerequisite for faithful chromosome segregation during mitosis. Finally, cohesin contributes to homologydirected repair of DNA breaks, in part, through holding the sister chromatid in proximity of the breaks and presenting it as the repair template (14).…”
mentioning
confidence: 99%